2010
DOI: 10.1017/s001708951000042x
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Closed 2-Orbifolds With Euler Characteristics

Abstract: Abstract. We determine the extent to which the collection of -Euler-Satake characteristics classify closed 2-orbifolds. In particular, we show that the closed, connected, effective, orientable 2-orbifolds are classified by the -Euler-Satake characteristics corresponding to free or free abelian and are not classified by those corresponding to any finite set of finitely generated discrete groups. These results demonstrate that the -Euler-Satake characteristics corresponding to free abelian constitute new invaria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is also of interest to consider the Γ-sectors of the orbifolds O 1 and O 2 for other free groups Γ. Since K 1 and K 2 are abelian, the Z 2 -sectors and the F 2sectors coincide; see [11]. The fact that the Z 2 -sectors coincide with the Z-sectors of the Z-sectors computed above (see [16, As the isotropy group of each point in O 1 and O 2 is abelian and can be generated by two elements, the Z ℓ -sectors of each O i for ℓ > 2 will simply yield multiple copies of the Z 2 -sectors of O i .…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also of interest to consider the Γ-sectors of the orbifolds O 1 and O 2 for other free groups Γ. Since K 1 and K 2 are abelian, the Z 2 -sectors and the F 2sectors coincide; see [11]. The fact that the Z 2 -sectors coincide with the Z-sectors of the Z-sectors computed above (see [16, As the isotropy group of each point in O 1 and O 2 is abelian and can be generated by two elements, the Z ℓ -sectors of each O i for ℓ > 2 will simply yield multiple copies of the Z 2 -sectors of O i .…”
Section: 2mentioning
confidence: 99%
“…It is also of interest to consider the Γ-sectors of the orbifolds O 1 and O 2 for other free groups Γ. Since K 1 and K 2 are abelian, the Z 2 -sectors and the F 2sectors coincide; see [11]. The fact that the Z 2 -sectors coincide with the Z-sectors of the Z-sectors computed above (see [16,Theorem 3.1]) makes it straightforward to compute the Z 2 -sectors of O 1 and O 2 .…”
Section: 2mentioning
confidence: 99%
“…In [Duval et al 2010], it was demonstrated that the collection of ‫ޚ‬ l -extensions of the Euler-Satake characteristic determine the diffeomorphism type of a closed, effective, orientable 2-dimensional orbifold and that infinitely many were required to do so. In addition, it was demonstrated that the χ ES corresponding to any collection of finitely generated discrete groups do not distinguish between certain effective, nonorientable 2-orbifolds.…”
Section: Ryan Carroll and Christopher Seatonmentioning
confidence: 99%